Developing a predictive model for determining the mechanical properties of CFB fly ash thermoset composite - Villa, Ralph P. (College of Engineering, University of the Philippines Diliman, 2014)
A predictive model was developed to determine the mechanical properties of CFB fly ash thermoset composite. Finite Element Method (FEM) using a two-dimensional RVE with single particle inclusion was utilized in modelling the mechanical response of the composite when subjected to tensile loading at different particle loading, particle shape and particle size conditions. Parametric studies indicate that the elastic modulus of the composite varies linearly with particle loading and exhibits a quadratic trend with respect to particle shape. However, for particle size, it was observed that it has negligible effect on the composite modulus. Multiple-linear regression was used to develop an empirical model relating the composite Young's Modulus to particle loading and particle aspect ratio. A quadratic model in terms of aspect ratio and particle loading was determined to be the best model to describe the system. Validation studies showed satisfactory agreement between model and experiment. Further analysis showed that for the CFB fly ash composite system, the quadratic model provided greater accuracy than other well-known micromechanical models such as the Halpin-Tsai and S-Combining Rule.